Pharmaceutical prokinetic and surgical interventions have opposing effects on gastroduodenal electromechanical coupling - Simmonds, Sam; Wang, Tim H.‐H.; Matthee, Ashton; Dowrick, Jarrah M.; Taberner, Andrew J.; Du, Peng; Angeli‐Gordon, Timothy R. (Acta Physiologica, 2025)
Improper gastric emptying is implicated in several gastrointestinal disorders and may result from disrupted electromechanical coupling of the gastroduodenal junction (GDJ). Rhythmic “slow waves” and myogenic “spikes” are bioelectrical mechanisms that, alongside neural and hormonal co‐factors, control GDJ motility. Aim To characterize the electromechanical effects of prokinetic (erythromycin) infusion and truncal vagotomy on pre‐clinical in vivo porcine models. Methods Following ethical approval, the GDJ was exposed in anesthetized crossbreed weaner pigs (N = 10), and custom high‐resolution electrodes were applied to the serosal surface. An EndoFLIP catheter (Medtronic, USA) was inserted orally and positioned across the pylorus to measure luminal diameter. In all subjects, control periods preceded intravenous infusion of erythromycin. In five of those subjects, truncal vagotomy was performed approximately an hour post‐infusion, before recording was resumed. Results Compared to control recordings, erythromycin increased contractile amplitude ([2.9 ± 1.1] mm vs. [2.2 ± 0.9] mm; p = 0.002) and was associated with more consistent gastric slow‐wave rhythms and increased amplitude of slow waves and spikes. Surgical vagotomy immediately decreased contractile amplitude ([2.90 ± 1.1] mm vs. [1.2 ± 0.6] mm; p = 0.049) and was associated with reduced slow‐wave amplitude, increased gastric and duodenal slow‐wave frequencies, and decreased spike patch coverage. Conclusions In conclusion, prokinetics and vagotomy produced opposing effects on GDJ electromechanical coupling and could inform diagnostic and interventional practices for patients with pathophysiological complications of this region.